Toenail arsenic species and metallome profiles associated with breast, cervical, prostate, and skin cancer prevalence in the Atlantic Partnership for Tomorrow’s Health cohort - Hood, Kalli M.; Sweeney, Ellen; Ilie, Gabriela; Keltie, Erin; Kim, Jong Sung (Frontiers in Public Health, 2023)
Introduction: Chronic exposure to arsenic through drinking water has been linked to several cancers. The metabolism of arsenic is thought to play a key role is arsenic-related carcinogenesis as metabolites of varying toxicity are produced and either stored in or excreted from the body. Atlantic Canada has the highest age-standardized incidence rates of all cancers in the country. This may be due to its high levels of environmental arsenic and the prevalence of unregulated private wells for water consumption. Here, we aimed to characterize the profiles of arsenic species and metallome in the toenails of four cancer groups, compare them to healthy participants (N=338), and assess potential associations between the profiles with cancer prevalence. Methods: This study employed a case-control design. Toenail samples and questionnaire data from cases (breast, cervical, prostate, and skin cancers) and controls were sourced from the Atlantic Partnership for Tomorrow’s Health (PATH) cohort study. The levels of arsenic species were measured using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) paired with High Performance Liquid Chromatography (HPLC) and total concentrations of metallome (23 metals) were determined by ICP-MS separately. Multivariate analyses compared cases with controls for each cancer group. Results: Arsenic speciation profiles varied by cancer type and were different between cases and controls in the breast (p=0.0330), cervical (p=0.0228), and skin (p=0.0228) cancer groups. In addition, the profiles of metallome profiles (nine metals) were differentiated in the prostate (p=0.0244) and skin (p=0.0321) cancer groups, with higher zinc concentrations among cases compared to controls. Conclusions: History of cancer diagnosis was associated with specific profiles of arsenic species and metallome. Our results indicate that arsenic methylation and zinc levels, as measured in toenails, may be an important biomarker for cancer prevalence. Further research is needed to use toenails as a prognostic measure of arsenic- and other metal-induced cancer.